The ethnomathematics of coastal communities as context for the development of learning modules in statistics and probability for the K-12 curriculum - Vallejo, Arnie Joy (Iloilo City University of the Philippines Visayas, 2019)
The way the subject mathematics is imparted among students across the globe is structured using a Western orientation since academic Mathematics is usually implicitly attached to the dominant Western mathematics. With the advent of ethnomathematics, the mathematics community of the 20th century proposed a culturally-relevant and culturally-responsive pedagogy through the field of ethnomathematics. However, Ethnomathematics s still i its exploratory phase, especially in the Philippines. This implies a derth of local and contextualized illustrations in Philippine mathematics textbooks. The main purpose of this study was to explore and investigate the ethnomathematics embedded in the culture along the coastal communities of the Province of Iloilo and subsequently develop contextualized learning modules on Statistics and Probability for the K to 12 Mathematics Curriculum for Grade 7 to 10. This wasaccomplished by documenting their cultural funds of knowledge through community immersion. This study was anchored on the Theory of Social Constructivism and employed the CoLab (Community as Laboratory) model in developing the contextualized learning modules. Field testing was conducted to determine the cognitive and affective impact of the contextualized learning modules to the student-learners through assessment tests and the ATMS questionnaire. Results report that ethnomathematics related to the field of Statistics and Probability wee found to be embedded and integrated in the activities in the community of Brgy. Punta Buri. The student-learners had apprehensions toward the learning modules but revealed that the contextualization of modules enhanced their appreciation of the value of mathematics. The integration of mathematical concepts in familiar contexts in familiar contexts enbled students to connect theoretical knowledge and cultural activities. In their current form, the developed modules still need improvement for them to serve as self-help leaning materials for indiviidualization of instruction. However, they may be utilized instead as supplementary learning materials for students.
Special Problem (MEd Math) -- Iloilo City : University of the Philippines Visayas, June 2019.